What do we Think About Water? Public Perception of the Current Situation of Water Resources in Costa Rica: an Indicator of Water Understanding and Management - Madrigal-Solís, Helga; Echeverría-Sáenz, Silvia; Pizarro-Mendez, Yanina; Alfaro-Chinchilla, Carolina; Jiménez-Cavallini, Sylvia; Centeno-Morales, Jacqueline; López-Alfaro, Nelly; Suárez-Serrano, Andrea (Uniciencia, 2020)
The objective of this research was to determine the level of knowledge and perception of the Costa Rican population about water for human consumption, general concepts, the impact of human activities, the occurrence of extreme events and water management and governance. In 2016, a quantitative-descriptive study of population perception was carried out through a semi-structured survey in which 800 people were consulted, through calls to landlines. It was found that the Costa Ricans: a) perceived that water is a public good and that there is greater availability of water than there is in reality, b) 22 % indicated having supply problems, infrastructure and/or water quality, c) are aware of the contamination of water bodies and willing to pay more for the treatment of wastewater, d) perceived a negative impact due to floods and landslides and, e) 55 % agreed that water for consumption comes from wells and springs, but only 12 % and 36 % had a general notion of what an aquifer and groundwater is, respectively. It is concluded that education programs should include general concepts on groundwater, water management and governance and that the willingness to pay more for wastewater treatment should be taken into consideration by the institutions for the improvement of environmental sanitation.